PENGELOLAAN PENGADUAN PELAYANAN PUBLIK BERBASIS E-GOVERNMENT (STUDI KASUS PENGELOLAAN PENGADUAN RAKYAT ONLINE DENPASAR PADA DINAS KOMUNIKASI DAN INFORMATIKA KOTA DENPASAR TAHUN 2014) - Yuni Lestari, Ni Luh; S.Fil.,MA, Bandiyah; Dwi Wismayanti, Kadek Wiwin (CITIZEN CHARTER, 2015)
ABSTRACT Public services based on e-Government in Indonesia has not been widely implemented. Denpasar government through the application of information technology and working to develop a system of complaints in the public service based on electronic media (online) integrated with a range of SKPD through Pengaduan Rakyat Online (PRO) Denpasar. Development Pengaduan Rakyat Online (PRO) Denpasar aims to accommodate and uniform handling of complaints in Denpasar government environment. The purpose of this study was to obtain the actual description of the management Pengaduan Rakyat Online (PRO) Denpasar and obstacles encountered in the implementation. The theory used in this research is the theory of public service management using the concept of electronic government. Methodology used in this study was qualitative exploratory. The findings of this research are: First, basically management Pengaduan Rakyat Online (PRO) Denpasar been running pretty good, but the service provided has not been entirely successful. This is due to lack of coordination, perception and interests regarding the policy. Secondly, the failure of these arrangements due to several constraints, among others: the flow of complaints in each agency is still done manually, Internet network in each agency sometimes impaired, and feedback from the public is still low in overseeing the complaints that have been submitted. On the other hand, the Pengaduan Rakyat Online (PRO) Denpasar is enough to help people in submitting the complaint because it can be accessed anywhere without the need to come directly to the institutions concerned. Keywords: Electronic Government, Public Services, Public Complaints